Akuntabilitas Pengelolaan Alokasi Dana Desa di Kecamatan Abiansemal Kabupaten Badung - Putu Tiwi Indriswari; I Made Wianto Putra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to examine the effect of the planning, implementation, accountability, and supervision on the accountability of village fund allocation management in Abiansemal. The population are government officers in 18 villages of Abiansemal with 72 people as using purposive sampling. The type of data used is quantitative data and analyzed by multiple linear regression. The results shows that the planning, implementation, and accountability have positive effect on the management of village fund allocations, but the supervision does not have positive effect on the management of village fund allocations in Abiansemal, Badung.